A STUDY ON UTILIZATION OF ANGIOTENSIN-CONVERTING ENZYME INHIBITORS AND ANGIOTENSIN RECEPTOR BLOCKERS IN PATIENTS WITH CARDIOVASCULAR DISEASES - Sood, Anuroop; Joseph, Jismi; Mathew, Sneha; K, Subramanyam; Ks, Rajesh; Raj Kc, Bharath (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objective of this study was to assess the prescribing pattern, most common indication, and adverse effects associated with angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in patients with cardiovascular diseases, and to identify the risk factors associated with cardiovascular diseases in a tertiary care hospital. Methods: A prospective observational study was carried out for a period of 6 months from October 2016 to March 2017 in both inpatients and outpatients of the cardiology department. Patients received either ACEIs or ARBs were enrolled in the study. The relevant details of the patients were collected from the patient case note and treatment chart and data analyzed. Results: Of 100 patients, 23.0% were female and 77.0% were male. Among them, majority of patients were in the age group of 41–60 years. Diabetes mellitus (39%), smoking (20%), and alcohol (14%) were the common risk factors. The most common indications of ACEIs were found to be ischemic heart diseases (IHDs) (17%) followed by hypertension (HTN)/IHD (12%), and IHD/heart failure (12%). Main indications of ARBs were found in HTN/ IHD (16%). Utilization of ACEIs (70%) was found to be higher when compared with ARBs (30%). Ramipril (69%) and telmisartan (18%) were the most commonly used ACEIs and ARBs, respectively. While analyzing the adverse effects of ACEIs and ARBs, about 5.71% of patients were identified with ramipril induced dry cough. Conclusions: The complications of cardiovascular diseases can be reduced by knowing the incidence of risk factors and alternative therapy can be initiated by assessing the incidence of adverse drug reactions related to ACEIs and ARBs